New homelands: Hindu communities in Mauritius, Guyana, Trinidad, South Africa, Fiji, and East Africa - Younger, Paul (Oxford University Press, 2010)
Mauritius : a parallel society -- Guyana : invented traditions -- Trinidad : ethnic religion -- South Africa : reform religion -- Fiji : a segregated society -- East Africa : caste religion